RELEVANSI MATERI HADIS PADA JURUSAN PAI DENGAN BAHAN AJAR QURAN HADIS PADA MADRASAH TSANAWIYAH - Hasbiyallah Hasbiyallah (Jurnal al-Thullab, 2016)
The relevance of the material on the tradition of religious (al-Hadis) teachers providers of Islamic Education Department greatly affect the success of education in madrasas. Therefore,material of hadis in the Quran Hadith curriculum MTs should always be the principal teaching materials at the Department of Islamic Education. This study used a qualitative research study in the reality of the curriculum at the Department PAI hadis and curriculum Quran Hadith on MTs. Based on the research that curriculum in the Department of PAI is not merely to prepare professional teachers in the field of study quran hadith, but covers the whole field of study PAI like moral theology, jurisprudence, Islamic history so that not all of the materials at the level of MTs tradition became part of the teaching material PAI majors. However, there is relevance as hadith studies teachers.